Narrativas sobre Límites, Comunicación, Cohesión y Relaciones Parentales en un Grupo de Madres con Hijos de 13 a 15 años Diagnosticados con Asma (2019)
In this research, an analysis of the narratives about the limits, communication, cohesion and parental relationships that a group of mothers manage, which have a child diagnosed with asthma, is carried out. The topic studied is highlighted by finding in the documentary review the current number of people suffering from asthma, which exceeds 5,272,038 people in Colombia according to the Ministry of Health in 2018, which is why this disease is a global problem of Public health, whose prevalence has increased in the last two decades without an apparent explanation, also presents the social impact of the disease in the family system and the way in which the family faces the situation, making itself present in the experiences that are handled from the family dynamics created through interaction.